Fungsi Bahasa dalam Wacana Ungkapan Hikmah di SD Se-Karesidenan Surakarta - Eko Purnomo; Agus Budi Wahyudi; Joko Santoso (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2021)
Surakarta Elementary Schools use many discourse expressions of wisdom as a medium for increasing literacy to students. This research is a qualitative research with a descriptive approach, because the data used is written discourse. The object of this research is the function of language in the expression of wisdom. The data source of this research is the expression hikamh which is located in SD Se-Karesidenan Surakarta. The data collection techniques were observation, listening and documentation, the researcher first conducted observations at SD Se-Karesidenan Surakarta, then observed the existing discourse of wisdom expressions and then recorded every wisdom expression that had a language function. The data analysis technique used the referential equivalent method. The data validation technique uses theoretical triangulation. The analysis results show that the wisdom expression contains 5 language functions, namely (1) instrumental function, (2) description function, (3) interaction function, (4) individual function, and (5) heuristic function.